Media release - Manzie, Daryl, 1946-
tag=1 data=MEDIA RELEASE tag=2 data=MANZIE, DARYL tag=8 data=HEALTH SERVICES tag=9 data=HEALTH SERVICESORIGINAL COMMUNITIES%CLOSE%PORT KEATSLY RIVERTHURST ISLAND tag=24 data=HEALTH & COMMUNITY SERVICES tag=27 data=M-0687-92 tag=61 data=25 tag=62 data=AUG tag=63 data=1992